Policy options for effective financing of university education in Nigeria: An international comparison approach (2016)
The debate about the task of financing education in general and universities in particular has continued to generate serious concern among stakeholders all over the world; and more specifically for developing countries like Nigeria. Despite various efforts in the country by successive governments at initiating policies that could enhance effective financing of the sector, there seems to be no significant improvement over the past decades. Adequate funding of universities is often believed to be one of the strong means for increasing the stock of human capital that is needed by a country for successful economic growth and development. However, in Nigeria, the problem of financing education in general and university education in particular is severe. For a long time now, the sector has contended with the challenges of inadequate funding by the government and other organizations. The problem of insufficient funding of universities is further complicated by the rising social and economic burden confronting the government in the face of declining economic fortunes and inflation riding education budget. This development has serious implication for university product quality and national output. The study is intended to advocate for globally effective policies that would improve education funding in Nigeria